INFORMAL COORDINATION AS SHADOW WORKFLOW: REWORK AND PROCESS FRICTION IN A SMALL FIRM IT ACCESS - Marcel, Marcel; Marzuqi, Tubagus Ahmad (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines how operational rework appears in internal access management in a small technology consulting firm in Jakarta, where work processes are still loosely organized. Using a mixed methods approach, the study reviewed 97 operational cases across six months and combined them with interviews with people directly involved in handling access issues. The analysis focused on access requests, password resets or account recovery, and escalations or handoffs, not general service complaints. The results show that the biggest burden comes less from the technical fix itself and more from three transition points: moving cases from WhatsApp to formal channels (41%), waiting for approval (48%), and handing cases to another person in charge (37%). Access requests faced the strongest approval barriers, while escalations and handoffs created the most repeated clarification, case transfers, and cases returning after they seemed finished. The interviews also show that WhatsApp often works as a shadow workflow: fast at the start, messy later when the initial context is not fully recorded, approvals depend on certain intermediaries, or a case looks closed even though the solution is only temporary. The novelty of this study lies in its practical view of rework through three layers, namely entry friction, processing friction, and closure distortion, along with a lightweight diagnostic that small companies can use to spot process waste without needing a complex evaluation system.